P182Involvement of ephrin-A1 in the migration and proliferation of endothelial cells. (15th July 2014) - Wiedemann, E; Jellinghaus, S; Ende, G; Augstein, A; Sczech, R; Strasser, RH; Poitz, D M
Abstract: The Eph-family, consisting of Eph-receptors and ephrin-ligands represents the largest class of receptor tyrosine-kinases. The role of Eph/ephrins in elementary physiological processes as re-endothelialisation is still not well understood. The aim of the present study was to investigate the regulation of the ligand ephrin-A1 and its potential impact on proliferation and migration of human umbilical venous (HUVEC) and arterial endothelial cells (HUAEC). Initially, it could be shown, that ephrin-A1 expression was positively correlated with the density of the endothelial cells. Thus, a significant induction of ephrin-A1 in endothelial cells was observed after contact inhibition. The impact of ephrin-A1 on endothelial proliferation and migration was studied using siRNA and adenoviral overexpression. The siRNA-mediated silencing of ephrin-A1 in HUVEC increased the proliferation. In contrast, adenoviral overexpression of ephrin-A1 decreased the proliferation, suggesting an involvement of ephrin-A1 in endothelial proliferation. To study the role of ephrin-A1 in processes associated with an endothelial defect, a wound healing assay was performed. Ephrin-A1-silenced HUVEC showed a faster gap area closure in comparison to cells transfected with a scrambled control siRNA. Interestingly, ephrin-A1-overexpressing endothelial cells showed a faster gap area closure compared to lacZ-control as well. Using live cell imaging it could be visualized that the silencing of ephrin-A1 influences the direction of the migration of HUVEC resulting in disorientation and a missing polarization of the cells. Overexpression of ephrin-A1 leads to a straight forward and faster migration compared to the controls. By using baculoviral expression of actin-GFP and talin-RFP accordingly both the silencing and the overexpression of ephrin-A1 resulted in an increased number of endothelial focal adhesions which also influenced the actin-cytoskeleton in endothelial cells. A migration assay was established to investigate endothelial response to contact with an ephrin-A1-coated surface. A temporary stop of migration was observed after surface coating with ephrin-A1-Fc. Taken together, these results show that ephrin-A1-expression depends on cell-density and is a critical determinant of endothelial proliferation. Furthermore, ephrinA1 is involved in the regulation of migration of cells, by modulating the speed of migration and more importantly the direction of migration. These results show, that ephrinA1 is highly involved in the process of wound healing which is amongst others of great importance for re-endothelialisation.